Examining folic acid intake: a cross-sectional study of pregnancy-related practices - Khan, Muhammad M.; Saad, Muhammad; Syed, Muhammad R.; Siddiqui, Farina F.; Siddiqui, Aisha R.; Rajput, Maisam A.; Siddiqui, Noor-us-Sahar; Sanaullah, Ifrah; Gul, Laraib; Ahmad, Muhammad (International Journal of Research in Medical Sciences, 2024)
Background: Folic acid supplementation during the periconceptional period is critical in preventing neural tube defects (NTDs) in the developing fetus. In Pakistan, a profound lack of awareness is seen regarding preventable pregnancy-related illnesses and the consequential high maternal and fetal mortality and morbidity rates. However, data from the surveys in the region of Sindh lacks inquiries regarding the baseline characteristics of the surveyed participants. Therefore, this study endeavoured to address this gap. Methods: Between October 2022 and April 2023, a cross-sectional study was conducted at two major tertiary care hospitals in Hyderabad and Jamshoro, Pakistan. A total of 374 participants, chosen by non-probability consecutive sampling, comprised the sample size. The association of demographic variables and knowledge, attitude, and practice of consumption of folic acid during pregnancy was determined using the χ2 test. A p value of less than 0.5 was considered statistically significant. Results: The mean age of the participants was 26.4±5.7 years. A total of 199 (53.20%) participants were literate, compared to 175 (46.79%) participants who were illiterate. Literate women fared better than illiterate women in all the metrics with a p-value of <0.001 and a Pearson correlation coefficient (r) of >0.7. Moreover, folic acid was consumed by only 38% of pregnant women during the periconceptional period. Conclusions: A substantial lack of knowledge regarding folic acid was found in the surveyed sample, significantly more marked in the illiterate faction. Additionally, the practice was rather unsatisfactory. However, the attitude remained encouraging.